Effectiveness of Diacutaneous Fibrolysis of Carpal Tunnel Syndrome in a Diabetic Patient: a case report - Hernández Secorún, Mar; Abenia Benedí, Hugo; Lucha López, María Orosia; Hidalgo García, César (Jornada de Jóvenes Investigadores del I3A, 2021)
Diabetic patients have a double risk factor for presenting Carpal Tunnel Syndrome (CTS). The aim of this study is to report the effectiveness of a Diacutaneous Fibrolysis programme in a diabetic patient suffering from CTS at short and medium-term.